Multifractal analysis of morphological changes in water bodies' structure by means of the satellite imagery processing - Artiushenko, М.V.; Tomchenko, О.V.; Pidgorniak, D.L. (Reports of the National Academy of Sciences of Ukraine, 2017)
A statistical method of description of the dynamics of water bodies' geomorphic structures with the use of satellite images is proposed. The method involves the multifractal properties of geosystem objects' spatial structures and is focused on the automated imagery processing, by using the information criteria of fractal spectra variability. The selection of information criteria to assess changes in object's spatial structure is based on properties of the statistical Renyi entropy. By means of the remote sensing, the multifractal analysis of changes that occurred in the sea part of Danube's delta coastline structure for a 30-year period is made.